Observational Evidence of the Basin‐Wide Gyre Reversal in the Gulf of Taranto. Issue 22 (13th November 2020) - Federico, I.; Pinardi, N.; Lyubartsev, V.; Maicu, F.; Causio, S.; Trotta, F.; Caporale, C.; Coppini, G.; Demarte, M.; Falconieri, A.; Lacava, T.; Lecci, R.; et al.
Abstract: The paper shows for the first time the observational evidence of basin‐wide gyre reversal in the Gulf of Taranto (north‐western Ionian Sea in the eastern Mediterranean Sea) by means of two specifically designed in situ oceanographic campaigns (based on CTD and ADCP measurements). The analysis of the in situ data shows a change in circulation from anticyclonic in October 2014 to cyclonic in June–July 2016. Furthermore, long‐term (1993–2018) analysis using gridded satellite altimetry data in the Gulf of Taranto shows that the cyclonic gyres are more frequent than anticyclonic gyres. The latter occur only for 2 to 3 years at a time in some decades. Plain Language Summary: The work shows the observational evidence of a phenomenon named gyre reversal (the circulation changes from cyclonic to anticyclonic), occurring in ocean regions with specific geometry characteristics, among others the Gulfs. In particular, our results unequivocally show for the first time the reversal of the basin‐scale gyre circulation in the Gulf of Taranto (north‐western Ionian Sea in the eastern Mediterranean Sea), by means of in situ oceanographic measurements and satellite data. Key Points: Observational evidence of a basin‐wide gyre reversal in the Gulf of Taranto, anticyclonic in October 2014 and cyclonic in June–July 2016 Long‐term satellite analysis suggests that, in the period from 1992–2018, cyclonic are more frequent than anticyclonic gyres Gyre currents undergo instabilities and formation of submesoscale and mesoscale eddies at the outer rim of the gyres